Building a Pipeline to Increase Academic Workforce Diversity to Achieve Health Equity (Mary Ann Liebert, 2021)
The disproportionately low number of under-represented minority (URM) faculty pursuing research careers is attributed partly to an inadequate pool of well-trained URM scientists. This is compounded by lower rates of successful competition for NIH funding by URM scientists. Evidence shows black scientists are 13% less likely to receive NIH funding relative to white scientists. Increasing the number of well-trained URM scientists is a highly significant goal, achievable through exposure to mentored learning opportunities in an autonomy-supportive academic network. In this article, the author describes his academic career trajectory leading to the establishment of the NHLBI-funded PRIDE Institute. The institute's overarching goal is to increase the number of URM scientists pursuing academic careers to address important cardiovascular health disparity issues. The PRIDE institute has been very successful in achieving 2020 Healthy People goals of a greater academic workforce diversity.